Salinity effect evaluation on the survival rate and hematology of snakeskin gourami juvenile Trichopodus pectoralis - Setijaningsih, Lies (Jurnal Akuakultur Indonesia, 2019)
ABSTRACT Snakeskin gourami Trichopodus pectoralis an endemic fish that was highly demanded by Indonesian society. The declining in population stock was the main problem cause its availability still relies upon the nature catch. The increase of its production of culture was still constrained by the slow rate of growth and survival rate in the seed phase. This study aimed to determine the optimal salinity and its effect on growth performance, survival rate, osmotic activity, and blood description of the snakeskin gourami Trichopodus pectoralis. A complete randomized design (CRD) was used in this study with four different treatments and each treatment consisted of three replications. The salinity test consists of 0 g/L, 1 g/L, 3 g/L, and 5 g/L. The experimental fish sized at 0.49 ± 0.13 g and length 2.96 ± 0.42 cm with a stock density of 25 fish/aquarium (1 fish/L). During 28-day of rearing, the experimental fish was fed using Tubifex sp. as restricted based on the FR (5%) of biomass per weekly sampling. The results showed that the optimal survival rate and growth showed the best at salinity 3 g/L because it showed the most stable blood level so that the fish could avoid stress response. Keywords: salinity, survival rate, growth, hematological, Trichopodus pectoralis  ABSTRAK Ikan sepat siam Trichopodus pectoralis merupakan ikan endemik yang sangat diminati masyarakat Indonesia.Pemenuhan kebutuhan ikan sepat siam masih mengandalkan hasil tangkapan dari alam sehingga populasi di alam mengalami penurunan. Peningkatan produksi ikan sepat siam dari budidaya masih terkendala dengan sintasan dan pertumbuhan yang lambat pada fase benih. Tujuan penelitian ini adalah menentukan salinitas optimum dan pengaruhnya terhadap performa sintasan, pertumbuhan, kerja osmotik, dan gambaran darah benih ikan sepat siam.Penelitian dilakukan dengan metode rancangan acak lengkap (RAL), empat perlakuan dan masing-masing3 kali ulangan. Perlakuan yang diujikan adalah salinitas 0 g/L, salinitas 1 g/L, salinitas 3 g/L, dan 5 g/L.Ikan yang digunakan berukuran 0,49±0,13 g dan panjang 2,96±0,42 cm, padat tebar masing-masing 25 ekor/akuarium (1 ekor/L). Selama 28 hari masa pemeliharaan, ikan sepat siam diberi pakan berupa cacing sutra (Tubifex sp.) secara restricted berdasarkan FR 5% dari biomassa per Sampling mingguan. Hasil penelitian menunjukkan sintasan dan pertumbuhan terbaik dihasilkan pada perlakuan salinitas 3 g/L. Hal itu diduga karena gambaran darah pada perlakuan 3 g/L stabil sehingga terhindar dari respon stres. Kata kunci: salinitas, sintasan, pertumbuhan, gambaran darah, sepatsiam